Translation and assessment of encultured meaning of the Multi-Dimensional Scale of Perceived Social Support in Diné bizaad (Navajo) using community-based participatory action research methods - Tapati Dutta; Jon Agley; Camille Keith; Gregory Zimet (Rural and Remote Health)
Introduction: Perceived social support is a psychological construct that is used to describe the 'perception of adequacy' of the support being provided by a person's social network. Higher perceived social support has been linked to multiple benefits across numerous studies over the past several decades and among multiple populations. The Multidimensional Scale of Perceived Social Support (MSPSS) is a 12-item scale to assess the construct of perceived social support. The instrument has been translated to approximately 35 languages and dialects, but it has rarely been translated into tribal languages, which may be commonly spoken in rural areas. Further, such translations have not always been accompanied by cultural adaptation. Assessment of the encultured meaning of terms from a validated instrument is important alongside translation because words and terms related to perceived social support can be culturally specific. As such, this article presents a community-engaged research approach to develop a translation of the MSPSS into Diné bizaad (Navajo), along with a qualitative assessment of the meaning and implications of key terminology from the instrument. Methods: This study was led by a faculty member at a Native American-Serving Nontribal Institution (NASNTI) in south-western Colorado, US. Additional research collaborators included the original developer of the English MSPSS, a researcher with experience in methodology, and a member of the local Navajo community who was a student at the NASNTI. Using convenience and snowball sampling, a 2.5-hour focus group discussion was conducted and audio-recorded in May 2023 with eight Navajo community members who met eligibility criteria (including fluency in both Diné and English). All participants provided consent and received gratitude gifts for completion. Participants were four males and four females with an age range of 30-60 years. Since the discussion and recording were bilingual, a written English and Diné transcription was produced and anonymized, then reviewed by researchers. It was then backward-forward translated to English, then checked with discussion participants to validate accuracy. Using the general inductive method, key concepts and codes were separately identified and documented using NVivo 21 by two researchers. Full consensus as to coding was achieved over a sequence of six iterative consensus meetings among the coders. Results: The project was able to produce a harmonized version of the MSPSS translated into Diné bizaad that accounted for variation in meaning and intent of multiple core concepts of perceived social support. For example, concepts of 'family' and 'friend' were often characterized by ethnic clan-based close-knit bonds. The concept of 'significant other' often meant 'spouse' but sometimes also meant someone who was highly trusted, especially among unmarried discussants. 'Social support' was trust-based rather than need-based and often relied on gender-concordant bonding. Many additional nuances were discussed and are outlined in the full study. Discussion: Navajo community members were excited to collaboratively work on making this screening tool available in Diné bizaad. The translation that emerged from this process likely differed from what would have emerged from a direct translation without community input. Next steps for the tool should include quantitative reliability and validity analyses.